2015
DOI: 10.1016/j.psychres.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hypothalamic–pituitary–adrenal axis dysregulation and insulin resistance in elderly patients with depression

Abstract: Cortisol dysregulation has been proposed to be involved in depression. Hypothalamic-pituitary-adrenal (HPA) axis dysregulation associated with major depressive disorder (MDD) was previously reported to be higher in the elderly. Furthermore, insulin resistance and the prevalence of type 2 diabetes are known to increase with aging. The aim of the present study was to determine whether a relationship existed between plasma cortisol levels following the dexamethasone/corticotrophin-releasing hormone (DEX/CRH) test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…A study of 4,333 middle-aged Japanese men suggested that depressive symptom were related to accumulation of visceral adipose, not subcutaneous adipose (Yamamoto et al, 2016). Potential mechanisms underlying these associations include hypothalamic-pituitary-adrenal axis (HPA-axis) dysregulation with hyper-cortisolemia (Yokoyama et al, 2015), inflammation (Miller et al, 2002), and the influences of lifestyle and behaviors (Lovell et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…A study of 4,333 middle-aged Japanese men suggested that depressive symptom were related to accumulation of visceral adipose, not subcutaneous adipose (Yamamoto et al, 2016). Potential mechanisms underlying these associations include hypothalamic-pituitary-adrenal axis (HPA-axis) dysregulation with hyper-cortisolemia (Yokoyama et al, 2015), inflammation (Miller et al, 2002), and the influences of lifestyle and behaviors (Lovell et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The neuroendocrine immune network, especially in the hypothalamic-pituitary-adrenal axis (HPA), is closely associated with T2DM. Glucocorticoid secreted by the HPA axis adversely regulates blood glucose homeostasis by disrupting the insulin signaling pathway and glucose metabolism [60]. Glucocorticoids increase blood glucose level by stimulating the gluconeogenesis of the liver and inhibiting glucose uptake by tissues.…”
Section: Role Of Nlrp3 Inflammasome In Dmmentioning
confidence: 99%
“…Chronic stress results in the dysregulation of hypothalamic-pituitary-adrenal (HPA) axis, which maybe one of the factors to MDD 17, 18 . The HPA axis, includes a feedback loop composed of the hypothalamus, pituitary and adrenal glands.…”
Section: Introductionmentioning
confidence: 99%